Budding of Enveloped Viruses: Interferon-Induced ISG15—Antivirus Mechanisms Targeting the Release Process - Eun Joo Seo; Jonathan Leis (Advances in Virology)
Pathogenic strains of viruses that infect humans are encapsulated in membranes derived from the host cell in which they infect. After replication, these viruses are released by a budding process that requires cell/viral membrane scission. As such, this represents a natural target for innate immunity mechanisms to interdict enveloped virus spread and recent advances in this field will be the subject of this paper.